MANGROVE RESOURCE USES BY LOCAL COMMUNITY IN INDONESIA - Cecep Kusmana; Sukristijiono Sukristijiono (Graduate School Bogor Agricultural University (SPs IPB), 2016)
Indonesia is an archipelagic country of more than 17,504 islands (28 big islands and 17,475 small islands) with the length of coastline estimated at 95,181 km, which bears mangroves from several meters to several kilometers. They are estimated at 3.2 million hectares growing extensively in the five big islands (Java, Sumatra, Kalimantan, Sulawesi, Papua) with various community types comprising of about 157 species (52 species of trees, 21 species of shrubs, 13 species of lyana, seven species of palms, 14 species of grasses, eight species of herbs, three species of parasites, 36 species of epiphytes, three species of ferns). The mangroves resources in Indonesia involve the flora, fauna, and land resources which are needed for supporting many kinds of human needs, especially for local community living in surrounding mangroves. For centuries, the Indonesian people have traditionally utilized mangroves. The most significant value of mangrove utilization is the gathering of forest products, classified into timber and non-timber products. The timber refers to poles and firewood, charcoal, and construction materials (e.g. housing material and fishing gears); the latter include tannin, medicines, dye, nypa thatch and shingles, nypa sap for vinegar and winemaking, and food drinks. Traditional uses of mangrove forest products are mainly the direct utilization of the products, usually in small scale. Beside of those, local community are used to utilizing associated mangrove aquatic fauna for supporting their daily life as well as utilizing mangrove habitat for multipurpose uses through agroforestry techniques (silvofishery, agrosilvofishery, agrosilvopastoralfishery systems). So that, the good mangrove ecosystem serves luxurious both flora and fauna species (biodiversity) as well as their abundance for signicantly supporting the welfare of coastal community